When "the" market loses its relevance: An empirical analysis of demand-side linkages in platform ecosystems - Bruno Carballa Smichowski; Néstor Duch-Brown; A. Gomez-Losada; Bertin Martens (European Commission, Joint Research Centre (JRC), 2021)
Recent literature has shown that the existence of supply and demand-side non-generic complementarities ("demand-side linkages") within ecosystems raises questions about the pertinence of defining a single relevant market comprising substitute products ("substitutability approach"). However, empirical methodologies to measure these linkages and asses the competitive dynamics underpinning them are lacking. Using recent data from internet traffic between the major 246 European digital platforms, we develop such a methodology and test some theoretical findings of the ecosystems literature with major implications for competition and regulatory analysis. We corroborate that demand-side linkages are a non-negligible phenomenon: 18% of these platforms show them. However, unlike what the ecosystems literature predicts, in roughly half of the cases they do not link complementors but platforms competing in at least one market. Finally, while, as expected, we observe demand-side linkages mostly within industry-defined ecosystems, we find evidence of industry-agnostic ecosystems. These could be instigated and orchestrated by platform users instead of by a firm. We conclude that the substitutability approach is not obsolete, but needs to be complemented with alternative approaches in order to i) take into account coopetition within the same relevant market and ii) analyze how the competitive process in one market can impact the welfare generated in another (industry's) market through non-generic complementarities.
Keywords: 330; ecosystems; platforms; complementarities; relevant market